2022
DOI: 10.3390/genes13081405
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Immune Profiles Can Represent the Tumor Immune Microenvironment Related to the Tumor Budding Histology in Uterine Cervical Cancer

Abstract: Tumor budding (TB) histology has become a critical biomarker for several solid cancers. Despite the accumulating evidence for the association of TB histology with poor prognosis, the biological characteristics of TB are little known about in the context related to the tumor immune microenvironment (TIME) in uterine cervical cancer (CC). Therefore, this study aimed to identify the transcriptomic immune profiles related to TB status and further provide robust medical evidence for clinical application. In our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Numerous previous studies have suggested that FCGR3B may be a risk factor for a range of autoimmune diseases, such as systemic lupus erythematosus and rheumatoid arthritis ( 28 ).The exact rationale for the role of FCGR3B in the treatment of CC is unclear. Yan and his team extracted and sequenced total RNA from 21 CC samples and showed that FCGR3B had high expression levels in these samples ( 29 ). This study confirms this observation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have suggested that FCGR3B may be a risk factor for a range of autoimmune diseases, such as systemic lupus erythematosus and rheumatoid arthritis ( 28 ).The exact rationale for the role of FCGR3B in the treatment of CC is unclear. Yan and his team extracted and sequenced total RNA from 21 CC samples and showed that FCGR3B had high expression levels in these samples ( 29 ). This study confirms this observation.…”
Section: Discussionmentioning
confidence: 99%